Taʿlīm al-mufradāt bi-istikhdām al-ṣuwar wa al-namādhij al-istiqrāʾiyyah (PWIM) li-tarqiyat qudrat al-talāmīdh ʿalā al-inshāʾ al-muwajjah - Hermawan, Acep; Kautsar, Ghisni (Kalamuna: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2022)
Based on student learning outcomes in learning Arabic vocabulary at MAN 1 Lebak Rangkasbitung Banten which is low. And the factors that cause the low is the background of students, interests and talents, student motivation. Therefore, teachers need the right media to achieve the main goal in learning Arabic vocabulary, its effect on guided writing using Picture Word Inductive Model media. The purpose of this study was to determine the students' ability in guided writing before and after using the Picture Word Inductive Model method, and to determine the improvement of student learning outcomes. The method used in this research is the experimental method of pretest and posttest design models. The result of the research is that student learning outcomes in guided writing before using the Picture Word Inductive Model method show the "Less" value category with a value of 50.83. The results after using the Picture Word Inductive Model are "Very Good" with a value of 83.05. And the use of Picture Word Inductve Model in Arabic vocabulary learning has an influence on students' ability in guided writing.